(untitled) (Asian Journal of Current Engineering and Maths, 2013)
Urban concentration and urban sprawl have important consequences on the environment. The anarchic sprawl of cities without green spaces, especially those of developing countries, is a true ecological threat to urban dwellers. The gradual change of microclimate in a large city is primarily related to the scarcity of green spaces. The main objective of this study is to assess the role of urban green spaces in alleviating the adverse effects of urbanization. The study is based on a 4 year series of measurements of the influence of the green spaces in Paris (France) on climatic factors and air pollution patterns. The analysis of these measurement samples revealed that green spaces enable the regulation of temperatures and the rate of significant pollution. The results of the study based on measurements, which represent the most frequent cases found during the campaign, indicate that urban green areas play an important role in improving the quality of the urban environment. The decreasing temperatures in green spaces promote the reduction of the urban heat island. Green spaces are the least polluted places in a city. They contribute significantly to the improvement of the microclimate and the reduction of the rate of pollution in the city.